Downregulation of the circadian rhythm regulator HLF promotes multiple-organ distant metastases in non-small cell lung cancer through PPAR/NF-κb signaling. (10th July 2020) - Chen, Jiarong; Liu, Aibin; Lin, Zhichao; Wang, Bin; Chai, Xingxing; Chen, Shasha; Lu, Wenjie; Zheng, Mingzhu; Cao, Ting; Zhong, Meigong; Li, Ronggang; Wu, Minyan; et al.
Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related death due to its early recurrence and widespread metastatic potential. Accumulating studies have reported that dysregulation of circadian rhythms-associated regulators is implicated in the recurrence and metastasis of NSCLC. Therefore, identification of metastasis-associated circadian rhythm genes is clinically necessary. Here we report that the circadian gene hepatic leukemia factor (HLF), which was dramatically reduced in early-relapsed NSCLC tissues, was significantly correlated with early progression and distant metastasis in NSCLC patients. Upregulating HLF inhibited, while silencing HLF promoted lung colonization, as well as metastasis of NSCLC cells to bone, liver and brain in vivo . Importantly, downexpression of HLF promoted anaerobic metabolism to support anchorage-independent growth of NSCLC cells under low nutritional condition by activating NF-κB/p65 signaling through disrupting translocation of PPARα and PPARγ. Further investigations revealed that both genetic deletion and methylation contribute to downexpression of HLF in NSCLC tissues. In conclusion, our results shed light on a plausible mechanism by which HLF inhibits distant metastasis in NSCLC, suggesting that HLF may serve as a novel target for clinical intervention in NSCLC. Highlights: HLF is downregulated in NSCLC and serves as a prognostic biomarker. Downexpression of HLF predicts early relapse and distant metastasis in NSCLC. Downexpression of HLF promotes anaerobic metabolism under low nutritional condition. HLF inhibits NF-κB/p65 signaling via increasing activity of PPAR. Genetic deletion and methylation contribute to downexpression of HLF in NSCLC.